(untitled) (International Journal of Psychosocial Rehabilitation, 2020)
In recent years, antibiotics (Abs) have been considered one of the most brilliant discoveries. During multiuse of these (Abs) in hospitals, food and beverage factories, and different cultures and communities, there is a clearly shown resistance to (Abs) due to the genetic ability of microbes for adaptation, especially after human manipulation processes in genetic engineering techniques for producing new resistant shapes, additionally through gene transfer from genome to other, making it more resistant either in medicine or agriculture. In this article, focusing on this evolution of microorganism resistance to drugs during the last 50 years and concentrating on its work, effectiveness, mode of action, and reasons that lead to this considerable resistance to medications, we investigate the extent of environmental microorganisms impact on the development of pathogenic microorganisms. Therefore, new methods for controlling these highly increased resistance types should be introduced. Also, the aim of this short review is to provide some thoughts on the role of clinical (Abs) in curing widespread diseases, not only in gathering huge amounts of beneficial information. Focusing on some recommendations for decreasing or restricting germ resistance for both physicians and patients.